ON CONOIDS IN CONSTRUCTION - VACKA, Milan; SMETANOVA, Dana (Trends in education, 2015)
In the paper we describe the use of knowledge from descriptive geometry in construction. Especially we present the use of conoid in construction practice. Ruled Surface conoid is often used as roof shape especially for industrial and commercial buildings and skylights in the shape of a building or dam to increase pressure resistance. In structural engineering practice the most common using of the conoids is illustrated in the attached figures. The intention of this article is to highlight and connect the interdisciplinary relationships between mathematics (respectively descriptive geometry) and practice (construction, architecture). Text can be used in the teaching or for popularizing purposes.
Keywords: ruled surface; conoid; roof structure.